Selecting the shape of supported metal nanocrystals: Pd huts, hexagons, or pyramids on SrTiO3(001). - Silly, F; Castell, M (2005)
Increasing interest in oxide supported nanoparticle science and technology is stimulating research into controlling nanocrystal shape. Pd forms nanocrystals on the surface of SrTiO3(001), and depending on the crystallographic interface of the Pd with the substrate three shapes can be created: truncated pyramids, huts, and hexagonal shaped disks. Scanning tunneling microscopy reveals that the nanocrystal shapes are determined by the substrate reconstruction and the substrate temperature during deposition. A thermodynamic model is used to show that the pyramids and huts are stable structures, and that the hexagons are trapped in a metastable state.